Effects of Lenvatinib treatment for advanced differentiated thyroid cancer on cortisol deficiency - Monti, Salvatore; Fazzalari, Beatrice; Renzelli, Valerio; Bongermino, Claudia; Lioni, Maria Francesca; Deiana, Maria Grazia; Poggi, Maurizio; Mori, Fedra; Pugliese, Giuseppe (Frontiers in Endocrinology, 2026)
BackgroundLenvatinib, a multi-kinase inhibitor widely used in the treatment of radioiodine-refractory differentiated thyroid carcinoma (RR-DTC), has shown remarkable efficacy and improvement in progression-free survival (PFS), although its use is associated with a variety of side effects. Among them, adrenal insufficiency (AI) remains under-recognized and potentially underestimated, and it may be involved in fatigue, one of the most frequent adverse events (AEs) Lenvatinib-related. In this prospective study, we report the incidence, development, and time course of primary AI (PAI) during Lenvatinib treatment in patients with RR-DTC followed at a single tertiary care center.MethodsThe study was conducted on 39 consecutive patients with RR-DTC. Eight patients were excluded because they had a follow-up of less than 6 months or were receiving glucocorticoids for RR-DTC-related indications. We studied 31 patients selected for Lenvatinib therapy from June 2017 to December 2024. The median follow-up duration was 42.58 ± 29.53 months (range, 6–97 months). Performance status was evaluated for each patient using the Eastern Cooperative Oncology Group (ECOG) scale. Adrenal function was assessed by measuring serum cortisol and adrenocorticotropic hormone (ACTH) levels, and through the 250 μg ACTH stimulation test. Additionally, fatigue intensity was evaluated using the Common Terminology Criteria for Adverse Events (CTCAE) grading scale. Peak cortisol levels below 500 nmol/L (18.1 µg/dL) at 30 or 60 minutes after ACTH injection were indicative of adrenal insufficiency (AI) (PAI-18.1). A cutoff of 386.2 nmol/L (14 µg/dL) has also been used (PAI-14). In patients with primary adrenal insufficiency (PAI), steroid replacement therapy with cortisone acetate (CA) was initiated at doses ranging from 25 to 37.5 mg/day. Throughout follow-up, the ACTH stimulation test was repeated every 3 to 9 months, with a 72-hour discontinuation of CA prior to testing.ResultsDuring Lenvatinib treatment, 24 of 31 patients (77.4%) developed primary AI (PAI)-18.1, and 14 of 31 patients (45.2%) developed PAI-14. Patients with a cortisol peak below 646.6 nmol/L at the initial ACTH stimulation test, prior to starting Lenvatinib, demonstrated a higher risk of developing both PAI-18.1 and PAI-14 during treatment. Patients who developed PAI during Lenvatinib treatment had significantly lower cortisol peak levels on the initial ACTH stimulation test performed before treatment initiation compared to those who did not develop PAI. Fatigue was observed in 28 of 31 patients (90%) during Lenvatinib treatment. Among patients who developed PAI, a significant improvement in fatigue was observed following initiation of CA therapy.ConclusionsOur findings suggest a higher occurrence of PAI, which may contribute to fatigue associated with Lenvatinib treatment. Routine adrenal function testing and early recognition of PAI are essential for timely diagnosis and effective glucocorticoid replacement therapy, enabling patients to continue Lenvatinib treatment with improved tolerability and adherence.